Practical synthesis of (+/-)-venlafaxine - Chavan, Subhash P.; Khobragade, Dushant A.; Thakkar, Mahesh; Kalkote, Uttam R. (Synthetic Communications, 2007)
A practical total synthesis of antidepressant (+/-)-venlafaxine is disclosed.
Keywords: antidepressant; Grignard reaction; Michael addition